(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the integration of core linguistic subsystems—phonology, morphology, syntax, semantics, and pragmatics—from a typological perspective. By examining how languages vary and converge in their structural layering and interaction among these subsystems, the study highlights crosslinguistic patterns and proposes a typological model that accounts for both autonomy and interdependence among language modules. Drawing on examples from typologically diverse languages, the research contributes to the broader understanding of linguistic architecture and its implications for universality and variation.